IMPROVING PRENATAL HEALTH COMMUNICATION: ENGAGING MEN VIA E-HEALTH - Damásio, Manuel; Catarino, Fernando; Ferreira, Paulo (PEOPLE: International Journal of Social Sciences, 2017)
The initial goal of this comparative study that aimed investigate the value of an e-health application to educate men about pregnancy-related health, involving EUA and Portugal, was to design an e-health intervention focused on the importance of prenatal health that would appeal to men and ultimately reinforce paternal involvement in pregnancy health. Through one-on-one in-person interviews with men that used the prototype of the application we could achieve a qualitative evaluation of perceived usefulness and ease of use of the web-based intervention for participants and how this influenced their behavioral intentions in relation with prenatal engagement. In the specific case of research conducted in Portugal, evaluation of e-Health literacy amongst the target group was never conducted in the past so, the specific results of the project in this aspect also contributed to knowledge in the field. The implementation of a cross-cultural, international comparative approach to the study of e-health interventions is highly original and although a very small sample was used, obtained results show the relevance of such type of research approach.